School Management Practices, Pupils’ Academic Achievement, and Teach-ers’ Work Performance During COVID-19 Pandemic - Fontillas, Efigenia; Cabal, Esmen M. (Future Science / FSH-PH Publications, 2023)
This study explored the perception of public-school teachers in Zone 1, Division of Zambales towards the management practices of the school heads during the COVID-19 Pandemic. Data on teachers’ work performance and the academic performance of the pupils were also considered. The researcher-made questionnaire was used as the data collection tool in a descriptive-survey research design with 352 public elementary school teachers. The school management practices included intra-school management and inter-school management practices. The study showed that the teacher respondents are rated outstanding in their work performance amidst COVID-19 and pupils attained a “Proficient” level of their academic performance as well. The study also revealed that there is no significant relationship between teachers' work performance and intra-school management practices, whereas there is a significant relationship between teachers' work performance and inter-school management practices. Furthermore, the study determined that there was a substantial correlation between the academic achievement of the students and the intra-school and inter-school management practices.